2015
DOI: 10.1007/s40489-015-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Emotion Processing in Children with Autism Spectrum Disorders: Neurobiological, Neuroendocrine, and Neurocognitive Considerations

Abstract: The understanding, expression, and regulation of emotion have been identified as core to everyday communication and psychosocial adjustment in children. The aim of this paper is to review and to compare current clinical and empirical knowledge on emotion recognition, reciprocity, and expression deficits in children diagnosed with autism spectrum disorders (ASD). The paper reviews current neurobiological, neuroendocrine, and neurocognitive explanations for the emotion-processing deficits seen in ASD, while cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 272 publications
0
29
0
Order By: Relevance
“…There are two different ways that researchers have sought to understand the physiological stress response in people with ASD. One area of research has examined whether common changes exist in the regular daily rhythms of cortisol secretion (Sivaratnam et al 2015 ). In most people, daily cortisol levels follow a general pattern, increasing significantly in the morning and then decreasing throughout the day.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…There are two different ways that researchers have sought to understand the physiological stress response in people with ASD. One area of research has examined whether common changes exist in the regular daily rhythms of cortisol secretion (Sivaratnam et al 2015 ). In most people, daily cortisol levels follow a general pattern, increasing significantly in the morning and then decreasing throughout the day.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, a specific altered pattern has not been found, possibly due to the significant heterogeneity within the autism spectrum (Taylor and Corbett 2014 ). Despite the absence of a particular alteration in daily cortisol rhythms, some type of dysregulation of the HPA axis in people with ASD has been a common finding across the literature (Sivaratnam et al 2015 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Despite atypical reciprocal social interactions, children with ASD might still be able to develop secure attachments to their primary caregiver [59], although reports are conflicting [60]. Reduced cognitive ability in addition to ASD core symptoms could be an important factor [61]. Nbea +/mice show impaired neurocognitive performance coinciding with increased hippocampal long-term potentiation and phosphorylation of the signaling protein CREB [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies conducted in ASD, research has shown that mothers' parenting style and parent–child reciprocity predict emotion regulation ability in children with ASD [Hirschler‐Guttenberg, Feldman, Ostfeld‐Etzion, Laor, & Golan, ; Hirschler‐Guttenberg, Golan, et al, ]. However, these studies did not exploit the underlying factors between parent–child interactions and the emotional ability of the children and, compared to TD populations, in ASD, these may involve a more complex interplay of factors [Sivaratnam et al, ]. Therefore, understanding parents' interaction with their children with ASD is of empirical and clinical relevance [Hirschler‐Guttenberg, Golan, et al, ].…”
Section: Parents' Role In Children's Emotional Difficultiesmentioning
confidence: 99%